Pengaruh Pemberian Es Krim Penambahan Tepung Kelor Terhadap Kadar Hemoglobin Remaja Putri di Kendari - Mayangsari, Riska; Rahayu Kasma, Andi Sri; Ihsan, Habib (Journal of Health Education and Literacy, 2023)
Adolescents are the group most vulnerable to anemia. Adolescents are categorized as anemic if their Hb level is <12 gr/dl. The prevalence of anemia in adolescents was 32% in 2018. Anemia can be caused by insufficient iron intake, menstruation, impaired absorption of iron, and the presence of infectious diseases. Increasing iron intake can be done by increasing local food intake. Moringa contains nutrients such as iron (fe), calcium (ca), vitamins A, β-carotene, protein, vitamins A, C, D, E, K, and B, and antioxidant compounds. Moringa can be processed into one of adolescents favorite snacks, namely ice cream. This study aims to determine the effect of giving ice cream with the addition of moringa leaf flour on the hemoglobin levels of female adolescents. This research was conducted with a one group pre post-test design. The sample in this study was 30 female adolescents. There is an effect of giving ice cream with the addition of Moringa flour on hemoglobin levels in young girls with a p-value of 0.002 (α<0.005). Giving ice cream with the addition of Moringa flour effects on increasing hemoglobin levels in female adolescents